ANÁLISE DO USO DO SOLO NA BACIA HIDROGRÁFICA DO CÓRREGO AVIAÇÃO EM BRASILÂNDIA-MS, BRASIL - Elias de Oliveira Junior (2023)
The focus of this work was to diagnose how land use and occupation can intervene in river basin areas, significantly altering the natural, physical, chemical and biological processes of natural river systems, since these sources integrate the various natural phenomena that occur in the area of these river basins. Therefore, the objective of this research was to analyze and evaluate the transformations of the different uses of land in a context of human intervention in the river environment and its surroundings with the help of Geographic Information System, geoprocessing and remote sensing techniques. For the morphological and morphometric characterization of the basin, the knowledge of Geomorphology applied by Christofoletti was used. To understand the study of land use and cover, the methodological procedures were based on digital processes through the interpretation of satellite images. The field work to collect the data proved the different uses of land interpreted by the images and desk work, as well as demonstrating that, directly or indirectly or through socioeconomic interests, human intervention causes changes in certain uses and coverage of the land. land, which generate serious environmental changes and economic activities aimed at production, such as monoculture, cause environmental imbalances and affect the river. Also, the study of basic water quality parameters demonstrated a lack of commitment to environmental legislation on water resources. The methodological proposal adopted proved to be efficient, since the research corroborated the understanding that human intervention in certain uses and soil covers in the Aviação stream watershed, highlighting pasture, sugar cane, housing and disposal of effluents directly into the watercourse without proper treatment caused changes in some water quality parameters in the Aviação stream. Keywords: Geographic Information System, land use and cover, water quality parameters.